Practical Considerations Relating to Routine Clinical Biomarker Testing for Non–small Cell Lung Cancer: Focus on Testing for RET Fusions - Herbst, Roy S.; Aisner, Dara L.; Sonett, Joshua R.; Turk, Andrew T.; Weintraub, Joshua L.; Lindeman, Neal I. (Frontiers in Medicine, 2021)
For patients with advanced non–small cell lung cancer, genomic profiling of tumors to identify potentially targetable alterations and thereby inform treatment selection is now part of standard care. While molecular analyses are primarily focused on actionable biomarkers associated with regulatory agency-approved therapies, there are a number of emerging biomarkers linked to investigational agents in advanced stages of clinical development. In particular, recently reported data relating to highly specific small molecule inhibitors of the proto-oncogene tyrosine-protein kinase receptor RET suggest that testing for tumor RET gene fusions in patients with NSCLC will become clinically important in the near future. As the number of biomarkers to be tested in NSCLC grows, it becomes increasingly important to optimize and prioritize the use of biopsy tissue, in order to both continue to allow accurate histopathological diagnosis and also to support concurrent genomic profiling to identify perhaps relatively uncommon genetic events. In order to provide practical expert consensus guidance to optimize processes facilitating genomic testing in NSCLC and to overcome barriers to access and implementation, a multidisciplinary advisory board was held in New York, on January 30, 2019. The panel comprised physicians involved in sample procurement (interventional radiologists and a thoracic surgeon), surgical pathologists specializing in the lung, molecular pathologists and thoracic oncologists. Particular consideration was given to the key barriers faced by these experts in establishing institutional genomic screening programs for NSCLC. Potential solutions have been devised in the form of consensus opinions that might be used to help resolve such issues.